Penerapan Aplikasi Mobile E-Card Employee Menggunakan Ionic Framework (Studi Kasus : PT. Darma Henwa, Tbk- Acp) - Bidah; Noor Islami, Raisa (mijournal.org, 2024)
PT. Darma Henwa, Tbk-ACP is a mining contractor company with various departments, including the Management Information System (MIS). Employee ID card data collection and verification are currently manual using Microsoft Excel, causing data to be disorganized and difficult to access. This research develops the